Synthesis and characterization of calcium and iron co-doped lanthanum silicate oxyapatites by sol-gel process for solid oxide fuel cells - Cao, X.; Jiang, San Ping; Li, Y. (Elsevier, 2015)
Lanthanum silicate oxyapatites with and without calcium (Ca) and iron (Fe) doping, La10Si5FeO26.5 (LSFO) and La9.5Ca0.5Si5.5Fe0.5O26.5 (LCSFO), are synthesized by sol–gel process (SGP) and solid state reaction process (SSP). The phase formation, microstructure and conductivities of LSFO and LCSFO oxyapatites are characterized by X-ray diffraction (XRD), scanning electron spectroscopy (SEM) and complex impedance analysis. The morphologies of LCSFO oxyapatite nanoparticles synthesized by SGP were characterized by transmission electron microscope (TEM). The thermal and decomposition properties of the LCSFO gel were analyzed by simultaneous differential scanning calorimetry and thermal gravimetric analysis (DSC–TGA). The results show that the phase formation of LCSFO synthesized by SGP occurs at temperatures as low as 750 °C, significantly lower than ~1500 °C required for LCSFO synthesized by SSP. Co-doping of Ca and Fe significantly improves the densification, sinterability and oxide-ion conductivity of lanthanum silicate oxyapatites. The best results were obtained on LCSFO synthesized by SGP, achieving oxide-ion conductivity of 2.08 × 10−2 S cm−1 at 800 °C, which is higher than 5.68 × 10−3 S cm−1 and 1.04 × 10−2 S cm−1 for LSFO and LCSFO synthesized by SSP, respectively, under the identical test conditions.